Palladium-Catalyzed One-Pot Approach to 3-(Diarylmethylene)oxindoles from Propiolamidoaryl Triflate - Dahye Lee; Sunhwa Park; Yoseb Yu; Kye Jung Shin; Jae Hong Seo (Molecules, 2015)
3-(Diarylmethylene)oxindoles have been synthesized from propiolamidoaryl triflate utilizing a palladium-catalyzed one-pot reaction consisting of three successive reactions: Sonogashira, Heck, and Suzuki-Miyaura. This method allows for the production of a complex skeleton of 3-(diarylmethylene)oxindole from propiolamidoaryl triflate using a commercially available aryl iodide and arylboronic acid in a simple and efficient way with moderate yield and stereoselectivity.